2009
DOI: 10.1007/s10750-009-9862-1
|View full text |Cite
|
Sign up to set email alerts
|

A conflict of morphological and genetic patterns in the Australian anostracan Branchinella longirostris

Abstract: Branchinella longirostris is a fairy shrimp endemic to ephemeral pools on granite outcrops in southwestern Australia. The patchy nature of its habitat is thought to result in a high degree of subdivision among populations, potentially promoting speciation. We combined traditional taxonomy with a molecular phylogeny of cytochrome c oxidase I (COI) to test whether B. longirostris could be a species complex and whether the frontal appendage on the second antennae of males is a suitable character to differentiate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 62 publications
2
28
0
Order By: Relevance
“…Taylor et al, 1996;Braga et al, 1999;Korn et al, 2006;Thum and Harrison, 2009;Zofkova and Timms, 2009;Ketmaier et al, 2012), the application of standard molecular evolutionary rates to freshwater microcrustaceans is to be used with caution, as it might overestimate the divergence times of the studied taxa. This is possibly due to the very short life span, fast generation time and peculiar life history of microcrustacean species, which might give many more chances to mutations to take place, Table S1 for site details).…”
Section: Some Remarks On Morphological and Molecular Evolutionary Ratmentioning
confidence: 99%
See 1 more Smart Citation
“…Taylor et al, 1996;Braga et al, 1999;Korn et al, 2006;Thum and Harrison, 2009;Zofkova and Timms, 2009;Ketmaier et al, 2012), the application of standard molecular evolutionary rates to freshwater microcrustaceans is to be used with caution, as it might overestimate the divergence times of the studied taxa. This is possibly due to the very short life span, fast generation time and peculiar life history of microcrustacean species, which might give many more chances to mutations to take place, Table S1 for site details).…”
Section: Some Remarks On Morphological and Molecular Evolutionary Ratmentioning
confidence: 99%
“…Knowlton and Weigt, 1998;Ketmaier et al, 2003). Furthermore, the possibility that mutagenic effects might act more incisively in shallow and ecologically-variable habitats has also to be considered: Zofkova and Timms (2009) suggested that the mutagenic effect of high UV exposure accelerates rates of molecular evolution in a fairy shrimp inhabiting shallow temporary ponds.…”
Section: Some Remarks On Morphological and Molecular Evolutionary Ratmentioning
confidence: 99%
“…The species known from Australia are listed below, together with their presently known distribution and habitat preferences. The validity of most has been confirmed by molecular analysis (Pinceel et al, 2013b (Note that the frontal appendage (i) shows increasing size and complexity within set patterns with age and (ii) shows some variation in structure between populations (Geddes, 1981;Zofkova and Timms, 2009). …”
Section: Streptocephlaus Queenslandicus Herbert and Timms 2000 New Combmentioning
confidence: 94%
“…Species in the genus Branchinella have been subjected to molecular studies (Zofkova and Timms, 2009;Pincel et al 2013a). For almost all species morphological differences are supported by differences in their DNA, though in the variable and isolated populations of B. longrostris on Western Australian inselbergs the structure of the frontal appendage is not aligned with their cytochrome c oxidase I differences.…”
Section: Classification and Main Taxonomic Featuresmentioning
confidence: 99%
“…in Gandolfi et al, 2015; Branchinecta ferox (Milne-Edwards, 1840) in Rodríguez-Flores et al, 2017, but see also Aguilar et al, 2017 for a plea for caution when attributing species rank to divergent clades) to a pronounced morphological diversity not paralleled by an analogous molecular diversification (which is suggestive of phenomena of morphological plasticity, e.g., Zofkova & Timms, 2009).…”
Section: Systematics and Phylogenymentioning
confidence: 99%